The Saga of the Masked Bobwhite: Lessons Learned and Unlearned - David E. Brown; Kevin B. Clark (National Quail Symposium Proceedings, 2017)
No bird has generated so much interest and controversy as has the masked bobwhite (Colinus virginianus ridgwayi). From its discovery in 1884 to the present, this gallinaceous game bird has captured the attention of hunter-naturalists, ornithologists, collectors, game breeders, conservationists and bureaucrats. Believed threatened with extinction throughout its 130 year history, the masked bobwhite prompted several collecting expeditions, a survey technique study, a plethora of propagation attempts, and the purchase of an 117,464 acre refuge by the federal government, and expenditures totaling millions of dollars. Yet, despite propagated stock existing in a captive facility on Buenos Aires National Wildlife Refuge, the status of the masked bobwhite is now more perilous than ever, and this subtropical race of America’s most popular game bird may now be functionally extinct. How this all came about is a lesson that needed to be learned by wildlife managers seeking to increase and secure wild populations of native game birds.
Keywords: Buenos Aires National Wildlife Refuge; Arizona; colinus virginianus ridgwayi; masked bobwhite; propagation; Sonora; Rancho Carrizo; restoration